2012
DOI: 10.5304/jafscd.2012.024.005
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the Local: Considerations for Higher Education Engagement with Community Food Systems

Abstract: Citation: Rosing, H. (2012). Demystifying the local: Considerations for higher education engagement with community food systems. Journal of Agriculture, Food Systems, and Community Development, 2(4) AbstractMany universities and colleges have started to channel resources toward understanding and supporting small-scale food systems development in low-income communities. These efforts are often embedded into institutional sustainability initiatives that incorporate new curricula, research agendas, and community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…More research is needed on successfully executed power analyses and, conversely, on what happens when organizations or institutions promoting "food justice" struggle or fail to come to terms with racial and class inequities. Rosing (2012) offers potential paths forward in this regard, suggesting that academics and activists embarking on food systems development embed that work within a social justice framework prior to initiating projects in lowincome communities.…”
Section: Beyond Foodmentioning
confidence: 99%
“…More research is needed on successfully executed power analyses and, conversely, on what happens when organizations or institutions promoting "food justice" struggle or fail to come to terms with racial and class inequities. Rosing (2012) offers potential paths forward in this regard, suggesting that academics and activists embarking on food systems development embed that work within a social justice framework prior to initiating projects in lowincome communities.…”
Section: Beyond Foodmentioning
confidence: 99%
“…Students and faculty need to approach community-university food projects with a critical perspective. The perception that people in economically distressed neighborhoods want to grow food and that helping them to build gardens and farms is a solution to food access challenges should be carefully and critically examined (Rosing, 2012). There is a problematic perception that growing food locally is the solution to food access challenges that are rooted in the global political economy, income inequality and, as Philip Howard suggests, the inordinate power of supermarkets in control of the food system (Howard, 2016, p.22).…”
Section: Resultsmentioning
confidence: 99%
“…Gray et al (2012) highlight the challenges of balancing the diverse needs and goals of funders, partners, and community members in a garden project at Santa Clara University. Rosing (2012) cautions academics to avoid extraction from local communities (via student training and data) and to avoid replicating nonprofit initiatives that align with neoliberal policies that disavow government responsibility for addressing social inequity. Bortolin's (2011) analysis of academic articles on service-learning found that even as academics espouse service to the community, they exploit the community for their own ends.…”
Section: Food Justice and Community-campus Engagementmentioning
confidence: 99%